Self‐Powered Flexible Sensor Based on the Graphene Modified P(VDF‐TrFE) Electrospun Fibers for Pressure Detection. Issue 12 (3rd October 2019) - Li, Ping; Zhao, Libo; Jiang, Zhuangde; Yu, Mingzhi; Li, Zhen; Li, Xuejiao
Abstract: Polymer P(VDF‐TrFE) has been extensively applied in modern flexible electronics, such as nanogenerators and pressure sensors. In this study, a repolarization method is proposed to exploit the piezoelectric properties of the P(VDF‐TrFE) electrospinning film modified by the reduced graphene oxide (rGO). Then, the repolarized composite film is applied as the self‐powered flexible pressure sensor. Notably, the piezoelectric output voltage and current of the repolarized composite film are up to 1.5 V and 0.125 µA, respectively. Typically, the piezoelectric voltage of the composite film is three times as high as that of the pure spinning film. Meanwhile, this composite film also exhibits piezoresistive effect, which is ascribed to the 3D network structure of the electrospun nanofibers. In addition, the highest piezoresistive sensitivity of the pressure sensor is 0.072 kPa −1 . To sum up, the pressure sensor fabricated in this study allows to simultaneously detect the static and dynamic pressure loads, which thereby has great application potentials in electronic skins (e‐skins) for human motion monitoring, such as motion state and finger bending. Abstract : A repolarization method is proposed to exploit the piezoelectric properties of the reduced graphene oxide (rGO) modified P(VDF‐TrFE) electrospinning film. The composite film is applied as a self‐powered flexible pressure sensor, can detect static and dynamic pressure. The output voltage and current are up to 1.5 V and 0.125 µA, three times as high as the ordinary electrospun film.